Penetration of Scheduled Commercial Banks in Rural Areas: A Comparative Study - Bansal, Puja; Behal, Vikas (Indian Journal of Finance, 2013)
Banking plays a vital role in the growth and development of developing countries like India. Banks lubricate the entire monetary and financial system and ensure smooth operations. With the initiation of the processes of liberalization and globalization of the economy, the financial sector, particularly the commercial banks, not only in urban areas, but also in rural areas were the first to experience the winds of change. However, these changes were experienced more in urban areas than in rural areas. The most pertinent issue today is how well is the rural banking sector positioned to cater to the continued growth of the banking sector as a whole? In India, more than 50 percent of the population is based in rural areas. Though the Indian banks are penetrating the rural areas to meet the rural customers’ needs, but still, they have not achieved the set target. In this light, there was a need to evaluate the performance of the banks working mostly in rural areas and compare with those that are not operating, or are involved on a very low scale in rural areas. The present paper throws light on the performance of the Scheduled Commercial Banks that have more branches and fewer branches in rural areas. The paper also highlights the main issues and suggests measures for the banks to penetrate the rural sector so that the Indian economy can grow as a whole.